Inhibition of human immunodeficiency virus type 1 replication is enhanced by a combination of transdominant Tat and Rev proteins. - Ulich, C (1996)
Mutation of either of two critical human immunodeficiency virus type 1 (HIV-1) regulatory proteins, Tat and Rev, results in marked defects in viral replication. Thus, inhibition of the function of one or both of these proteins can significantly inhibit viral growth. In the present study, we constructed a novel transdominant Tat mutant protein and compared its efficiency in inhibiting HIV-1 replication with that of transdominant mutant Rev M10 when these proteins were stably expressed either alone or in combination in T-lymphocyte cell lines. The transdominant Tat mutant protein alone resulted in a modest inhibition of HIV replication, but it was able to enhance the ability of the M10 Rev mutant protein to inhibit HIV-1 replication. These results suggest a possible synergistic effect of these transdominant mutant proteins in inhibiting HIV-1 replication.